The low-FODMAP diet - Paula Lucas Zapata; Esther García Navarro; Carmen Ribes Koninckx (Elsevier, 2024)
In this article we present a protocol for the use of the low-FODMAP diet in paediatric patients and review of the current evidence on its efficacy. These short-chain carbohydrates, which can be fermented by the intestinal microbiota, are found in a wide variety of foods, mainly of plant origin. The low-FODMAP diet is a therapeutic tool used for the management of gastrointestinal disorders such as irritable bowel syndrome. The sources we used were PubMed, Web of Science, Google Scholar and institutional websites. Following consumption of FODMAP-rich foods, a series of end products are generated that are not absorbed, giving rise to symptoms. Before starting a low-FODMAP diet, it is important to carry out a diagnostic evaluation including any applicable tests. Treatment is structured in 3 phases: elimination, reintroduction and personalization phase. In the first phase, FODMAP-rich foods are eliminated for 2-3 weeks. In the second phase, lasting 8 weeks, FODMAP-rich foods are gradually reintroduced. The last phase consists in customizing the diet according to individual tolerance. This article details which foods contain FODMAPs and possible substitutes. In addition, specific food diary/intake tracking and educational materials are provided in a series of appendices to facilitate adherence to the diet. Although most studies have been conducted in adults, there is also some evidence on the beneficial effects in the paediatric age group, with a reduction of symptoms, especially in patients with functional gastrointestinal disorders. Nevertheless, more research is required on the subject. Resumen: En este artículo presentamos un protocolo para el uso de la dieta baja en FODMAPs en pacientes pediátricos y una revisión sobre la evidencia actual de su eficacia. Estos hidratos de carbono de cadena corta, fermentables por el microbiota intestinal, se encuentran fundamentalmente en gran variedad de alimentos de origen vegetal. La dieta baja en FODMAPs es una herramienta terapéutica utilizada en trastornos digestivos como el síndrome del intestino irritable. Los recursos utilizados han sido PubMed, Web of Science, Google Scholar y páginas web oficiales. Tras el consumo de alimentos ricos en FODMAPs, se generan unos productos finales que no se absorben, causando sintomatología. Antes de comenzar dicha dieta, es importante realizar una aproximación diagnóstica a través de las pruebas complementarias pertinentes. El tratamiento se divide en 3 fases: eliminación, reintroducción y personalización. En la primera se eliminan los alimentos ricos en FODMAPs durante 2-3 semanas. La segunda dura 8 semanas, y en ese período se introducen de nuevo de forma gradual alimentos ricos en FODMAPs. La última fase consiste en personalizar la dieta según la tolerancia individual. En este artículo se detallan aquellos alimentos que contienen dichos compuestos y los posibles sustitutos. Además, en una serie de Anexos se incluyen registros dietéticos específicos, y material didáctico para facilitar el cumplimiento de la dieta. Pese a que la mayoría de estudios se han realizado en población adulta, se ha observado que en edad pediátrica también tiene efectos beneficiosos. No obstante, se requiere más investigación al respecto.